(untitled) (American Journal of Technology and Applied Sciences, 2023)
Almond lives on average 25-30 years. On one hectare of land with 100-120 almond trees, an average yield of 350-500 kg is obtained. 1000-1500 kg/ha can be obtained from the area with proper agrotechnics and care. However, under the influence of fungal diseases, the fruit of almonds is damaged and productivity decreases. Below is the effect of the fungus Stigmina carpophila (Lev.) on almond fruit.